A new detector for the beam energy measurement in proton therapy: a feasibility study. (5th November 2020) - Vignati, A; Giordanengo, S; Milian, F Mas; Ganjeh, Z Ahmadi; Donetti, M; Fausti, F; Ferrero, M; Ali, O Hammad; Villarreal, O A Martì; Mazza, G; Shakarami, Z; Sola, V; et al.
Abstract: The proof of concept of a new device, capable of determining in a few seconds the energy of clinical proton beams by measuring the time of flight (ToF) of protons, is presented. The prototype consists of two thin ultra fast silicon detector (UFSD) pads, aligned along the beam direction in a telescope configuration and readout by a digitizer. The method developed for extracting the energy at the isocenter from the measured ToF, validated by Monte Carlo simulations, and the procedure used to calibrate the system are also presented and discussed in detail. The prototype was tested at the Centro Nazionale di Adroterapia Oncologica (CNAO, Pavia, Italy), at several beam energies, covering the entire clinical range, and using different distances between the sensors. The measured beam energies were benchmarked against the nominal CNAO energy values, obtained during the commissioning of the centre from the measured ranges in water. Deviations of few hundreds of keV have been achieved for all considered proton beam energies for distances between the two sensors larger than 60 cm, indicating a sensitivity to the corresponding beam range in water smaller than the clinical tolerance of 1 mm. Moreover, few seconds of irradiation were necessary to collect the required statistics. These preliminary results indicate that a telescope of UFSDs could achieve in a short time the accuracy required for the clinical application and therefore encourage further investigations towards the improvement and the optimization of the present prototype.